Models and Theories of Health Education and Health Promotion in Physical Activity Interventions for Women: a Systematic Review - Seyed Mohammad Mehdi Hazavehei; Shohreh Emdadi; Mehdi Khezeli (Journal of Education and Community Health)
Introduction: The present study as a systematic review investigated and analyzed interventions based on models and theories of health education and promotion in the field of physical activity in women. Materials and Methods: Three electronic databases, including Springer, Biomed Central and Science Direct were searched systematically. Only studies were selected that were quantitative, interventional and in English language as well as those that used at least one of the models and theories of health education and health promotion. Finally, 13 studies were reviewed that met the inclusion criteria and published from 2000 to 2013. Results: Of 13 studies reviewed, 10 studies measured levels of physical activity before and after the intervention, which nine interventions increased physical activity in the intervention group compared to the control group. Studies were conducted in different settings of health promotion including health care centers, community setting and workplace. The most widely used model was the Transtheoretical Model applied in eight of investigations. Conclusion: It is suggested to focus more on physical activity and duration of interventions to increase the efficacy of interventions. It is suggested to measure changes of physical activity habits in experimental and control groups in interventions based on the transtheoretical model to prepare a complementary scale to assess the efficacy of interventions. According to the results, no study had focused on changes in institutional policies or general health or providing changes in environment related to physical activity.